2020
DOI: 10.3390/ijerph17010300
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Parameters of Hemostasis, Adhesion Molecules, and Inflammation in Type 2 Diabetes Mellitus: Correlation with Glycemic Control

Abstract: Background: Type 2 diabetes mellitus (T2DM) is characterized by a prothrombotic state, predisposing to vascular complications. Some related markers, linking thrombophilia to hemostasis and inflammation, however, have been poorly explored in relation to patients’ glycemia. We therefore investigated the association of laboratory hemostatic parameters, circulating adhesion molecules (ADMs), white blood cell (WBC) count, and neutrophil/lymphocyte ratio (NLR) with T2DM and glycemic control. Research design: In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 44 publications
7
16
0
1
Order By: Relevance
“…Taken together, the results of the present study could be explained by increased IR and carotid atherosclerosis [6,51]. Insulin resistance was related to endothelial dysfunction, alterations in hemostatic process, and inflammation [51]. These pathogenic changes could increase the risk of CVD [51].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Taken together, the results of the present study could be explained by increased IR and carotid atherosclerosis [6,51]. Insulin resistance was related to endothelial dysfunction, alterations in hemostatic process, and inflammation [51]. These pathogenic changes could increase the risk of CVD [51].…”
Section: Discussionsupporting
confidence: 63%
“…In a recent study on the Vascular-Metabolic CUN cohort [18], a higher TyG index resulted in a higher risk for incident ischemic stroke, whereas Zheng et al did not find an association between the TyG index and CVA events [33]. Taken together, the results of the present study could be explained by increased IR and carotid atherosclerosis [6,51]. Insulin resistance was related to endothelial dysfunction, alterations in hemostatic process, and inflammation [51].…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…Clinical studies have evidenced an impaired endothelium-dependent dilatation in both T2D patients [180] and related high-risk conditions, including obesity, prediabetes or first-degree familial history of diabetes [181][182][183]. According to current understanding, endothelial dysfunction is associated with oxidative stress and reduced nitric oxide bioavailability, increased anticoagulant properties and platelet aggregation, increased expression of adhesion molecules (i.e., P-and E-selectin, intercellular adhesion molecule-1 (ICAM-1) and leukocyte adhesion molecules [i.e., vascular cell adhesion molecule-1 (VCAM-1), increased secretion of proinflammatory chemokines (monocyte chemotactic protein (MCP-1), and cytokines (i.e., IL-1b, IL-6, IL-8, TNF-a)] [184,185]. A systematic review and meta-analysis [186] reported that a regular consumption of EVOO (approximately between 1 and 50 mg daily) could favorably affect circulating inflammatory biomarkers, known as acute-phase reactants, and the flow-mediated vasodilation, thus contributing to the CVD protective effects of the MedDiet, observed in epidemiological studies [37,38].…”
Section: Influence Of Polyphenols On Endothelial Dysfunction and Athementioning
confidence: 99%
“…Neutrophils are the most abundant type of white blood cell and are reported as active players in inflammation of obesity-related insulin resistance [2]. Additionally, neutrophil count, a marker of subclinical inflammation, has been shown to significantly increase in type 2 diabetes compared with healthy subjects [3][4][5]. Neutrophil-lymphocyte ratio significantly increases in prediabetes and diabetes and may be a predictive marker for prediabetes and diabetes mellitus [6].…”
Section: Introductionmentioning
confidence: 99%